A review of the family Eucharitidae (Hymenoptera: Chalcidoidea) of Egypt - Gadallah, Neveen S.; Edmardash, Yusuf A.; Heraty, John M. (Zootaxa, 2013)
The species of Eucharitidae (Hymenoptera: Chalcidoidea) of Egypt are reviewed. Three species of Eucharis Westwood are reported, Eucharis (Eucharisca) bytinskisalzi Bouček, E. (Psilogastrellus) cuprea (Blanchard) and E. (Psilogastrellus) punctata Förster. Primary type material of E. bytinskisalzi and E. cuprea is illustrated through macrophotography and a key to separate the three species is provided. Eucharis bytinskisalzi is listed as a new record for the Egyptian fauna.